MORPHOLOGICAL CHANGES IN THE LIVER IN NORMAL AND CHRONIC ALCOHOL POISONING - Khamroev Khudoyshukur Nutfilloevich; Khasanova Dilnoza Akhrorovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Purpose of the study: to assess the morphological changes in the liver in normal and chronic alcohol poisoning and the features of its changes. Materials and methods: to solve the set tasks and achieve the goals, it is planned to use experimental, histological, morphometric, and statistical research methods. It was obtained from 90 adult white rats of both sexes, weighing 180-280 g, which were quarantined for 14 days in the experimental vivarium. The feeding of the animals will consist of a standard food ration. All animals are divided into 3 groups.